The quest for the ganglioside functions; what did we learn more from «evo-devo» or signaling of long-term maintenance? - Heffer-Lauc, M.; Mojsovic-Cuic, A.; Hrabac, P.; Viljetic, B.; Dikic, D. (Вiopolymers and Cell, 2010)
Gangliosides are characteristic extracellular-facing plasma membrane determinants in vertebrate brain. The four major gangliosides (GM1, GD1a, GD1b and GT1b) dominate among more than one hundred glycolipid structures in nervous tissue. During brain development the expression of simple gangliosides shifts toward more complex ones, accompanied by a multiple increase in their total amount. The shift is precisely regulated and some specific structures represent well established neurodevelopmental milestones. From the evolutionary perspective, the ganglioside content in fish and amphibian brain is significantly lower than in mammalian brain, but the general variability is greater. More-polar structures, abundant in Antarctic fishes, are rare in higher vertebrates or expressed only in a narrow developmental frame. Reptiles, birds and mammals share identical common structures expressed in similar patterns with minor interspecies differences. On the contrary, fish and amphibian brains show significant interspecies differences in amount, structure and expression patterns. The initial assumption of evolutionary studies was that the variations in lipid content, particularly the glycolipid content, during temperature adaptations in ectothermic and hibernating heterothermic animals, represent an efficient molecular mechanism of the membrane function preservation. Studies of ordered lipid domains in the last decade verified the ganglioside-mediated regulation of membrane proteins (receptor kinases, neurotransmitter receptors and ion channels) as well as receptor-ligand interaction important for cell signaling.